Population pharmacokinetic modeling of zavegepant, a calcitonin gene‐related peptide receptor antagonist, in healthy adults and patients with migraine - Craig M. Comisar; Jose Francis; Jim H. Hughes; Rajinder Bhardwaj; Richard Bertz; Jing Liu (CPT: Pharmacometrics & Systems Pharmacology)
Abstract Zavegepant (ZAVZPRET™) is a high‐affinity, selective, small‐molecule calcitonin gene‐related peptide receptor antagonist available for acute treatment of migraine in adults. A population pharmacokinetic analysis was performed to describe zavegepant plasma concentration–time course, characterize bioavailability, and identify covariates affecting zavegepant exposure. The model was developed and validated using data from 10 phase I clinical studies, wherein zavegepant was administered intravenously, intranasally, or orally to healthy adults and patients with migraine. Plasma concentration–time data were analyzed using nonlinear mixed‐effects modeling. A three‐compartment model with first‐order elimination from the central compartment, and sequential zero‐ and first‐order absorption best described the observed plasma concentration–time course of zavegepant. Bioavailability was 5.1% and 0.65% for intranasal and oral treatment, respectively; absorption rate constants were 5.8 and 0.8 h−1, respectively. Body weight‐based empirical allometric scaling was applied using standard exponents (0.75 for clearance and 1 for volume of distribution). Age (range 18–71 years), race, ethnicity, sex, renal function, and co‐administration of oral contraceptives or sumatriptan did not significantly change zavegepant pharmacokinetics. Moderate hepatic impairment (Child‐Pugh score 7–9) or co‐administration of rifampin decreased elimination clearance of oral zavegepant by ~40%. The zavegepant population pharmacokinetic model adequately characterized zavegepant concentration–time profiles, the bioavailability of intranasal and oral zavegepant, as well as the effect of intrinsic and extrinsic factors on zavegepant pharmacokinetics.